2015
DOI: 10.3758/s13414-015-0885-6
|View full text |Cite
|
Sign up to set email alerts
|

Rhesus macaques (Macaca mulatta) exhibit the decoy effect in a perceptual discrimination task

Abstract: The asymmetric dominance effect (or decoy effect) is a form of context-dependent choice bias in which the probability of choosing one of two options is impacted by the introduction of a third option, also known as the decoy. Decoy effects are documented widely within the human consumer choice literature and even extend to preference testing within nonhuman animals. Here, we extended this line of research to a perceptual discrimination task with rhesus monkeys to determine whether decoy stimuli would impact siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
49
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(58 citation statements)
references
References 37 publications
2
49
3
Order By: Relevance
“…In this study, researchers found no evidence for the decoy effect using an innovative task preference paradigm in rhesus macaques (Parrish, Afrifa, & Beran, this issue), despite previous findings of such an effect in the same species using a perceptual paradigm (Parrish, Evans & Beran, 2015). Such results are important in delineating the extent and boundaries of cognitive phenomena.…”
contrasting
confidence: 42%
“…In this study, researchers found no evidence for the decoy effect using an innovative task preference paradigm in rhesus macaques (Parrish, Afrifa, & Beran, this issue), despite previous findings of such an effect in the same species using a perceptual paradigm (Parrish, Evans & Beran, 2015). Such results are important in delineating the extent and boundaries of cognitive phenomena.…”
contrasting
confidence: 42%
“…Alternatively, if the decoy rectangle's orientation was incongruent with the truly largest rectangle, performance suffered (e.g., the decoy and second-to-largest rectangle were longer in the horizontal plane, increasing likelihood of selection of the latter). These comparative results from Parrish et al (2015) indicated that rhesus monkeys responded similarly to decoy stimuli in a perceptual discrimination task as human adults (Trueblood et al, 2013). The use of this version of a perceptual decoy paradigm also highlighted that context effects of this nature are not exclusive to complex decisionmaking, such as consumer choice behavior or political elections, or to inherently valuable and prepotent stimuli common for comparative tasks, such as choices among appetitive food options.…”
mentioning
confidence: 95%
“…In our previous work investigating choice behavior among primates, we presented rhesus macaques (Macaca mulatta) with a computerized perceptual discrimination task to investigate the decoy effect as the first study to assess this phenomenon in a nonhuman primate species (Parrish et al, 2015). We were interested in whether decoy effects might emerge using a relatively simple perceptual choice task modified from the human literature (Trueblood, Brown, Heathcote, & Busemeyer, 2013), which would provide further support for the idea that these decisional biases are early emerging, quickly generated, and widespread across contexts.…”
mentioning
confidence: 99%
“…The response time data in that experiment (Parrish et al, 2015b) also were interesting. When monkeys made a correct choice of the largest rectangle, they did so the fastest when a "helpful" decoy was present (i.e., the decoy matched the orientation of the truly larger of the other two rectangles).…”
Section: Biases and Context Effectsmentioning
confidence: 83%
“…We presented rhesus monkeys with a size discrimination task (Parrish, Evans, & Beran, 2015b). This approach came from work with humans in which they were asked to judge the size of rectangles in various orientations (Trueblood, Brown, Heathcote, & Busemeyer, 2013).…”
Section: Biases and Context Effectsmentioning
confidence: 99%